AUSTRIAN – UKRAINIAN PROJECT CENREC AS EXAMPLE OF INFORMATION SUPPORT OF ACTIVITY OF INTERNATIONAL SCIENTIFIC COMMUNITY. - E. Kartashova; M. Lvov (Ìнформаційні технології в освіті, 2009)
In the paper the problem of informational support and international scientific activity and cooperation of a few research groups working in the same scientific area is considered. Each such group includes scientific adviser, collaborators, postgraduate and master students. The problem consists in effective support of its collaboration. As an example of support environment of joint scientific activity we consider the portal CENREC, developing in the frame of joint project of research institute of symbolic computations of J. Kepler University (Linz, Austria) http://risc.uni-linz.ac.at/ and research institute of information technologies of Kherson State University (Ukraine). The project was initiated by authors in 2008. Since 2009 the project is supported by ministers of science and education of Austria and Ukraine.